Pemanfaatan Air Cucian Beras Sebagai Pupuk Untuk Pertumbuhan Tanaman Sawi Hijau (Brassica juncea L.) - Ana Muslimah; Syamsul Rizal; Marmaini Marmaini (Universitas PGRI Palembang, 2023)
This research was conducted at the FST Workshop at PGRI Palembang University. The time of the study starts from May to June 2021. This type of research is an experimental study using the Completely Randomized Design (CRD) method consisting of 5 treatments and 5 replications, so there are 25 treatment units. The treatments consisted of: (P0) with a dose of 0 ml, (P1) with a dose of 100 ml of rice/plant washing water, (P2) with a dose of 200 ml of rice/plant washing water, (P3) with a dose of 300 ml of rice washing water. /plant, and (P4) with a dose of 400 ml of rice washing water/plant. The variables observed in this study were plant height, number of leaves, and wet weight of mustard greens (Brassica juncea L.). The results showed that the rice washing water treatment on the growth and yield of mustard greens (Brassica juncea L.) did not have a significant effect on increasing the number of leaves of mustard greens, but had a significant effect on the growth of plant height and wet weight of mustard greens (Brassica juncea L.) .).